(untitled) (World Bulletin of Social Sciences, 2025)
As we learn any language, achieving the ability to communicate freely in the language being studied is considered a rewarding goal. For this reason, various methods have been developed for the development of oral speech, before thinking about oral speech, we found it necessary to look at what linguometodics is.